The reality of Hausa low tone raising a response - Russell G. Schuh (LibraryPress@UF, 1989)
Paul Newman and Philip Jaggar in an article in this issue of Studies in African Linguistics argue that a rule of Low Tone Raising (L TR), proposed in Leben [1971] is not a synchronic rule in Hausa. This rule, as originally fonnulated in Leben [1971], raises a final low tone (L) of a word if the syllable bearing the L (1) follows a L and (2) has a long vowel. I agree with them that L TR is not a rule; indeed, contrary to their assumption (first paragraph of §2), I would claim that it never has been a rule. The question which I wish to raise is whether there is any synchronic (and/or historical) reality to the phenomenon which originally attracted Leben's attention.